The influence of fandom culture, social media and viral marketing on the popularity of the Film Mencuri Raden Saleh which causes Fear Of Missing Out (FOMO) symptoms in Indonesian society - Iqlima Az-Zahra Ciersya; Nur Afifah; Bintoro Bagus Purmono; Ramadania Ramadania; Karsim Karsim (Trigin Publisher, 2023)
This research aims to investigate the influence of three main factors, namely Fandom Culture, Social Media, and Viral Marketing, on the popularity of the film